Student nurses' lived experiences of caring for women undergoing a termination of pregnancy - Exley, Rose (2014)
Abstract Background and literature - It has been widely recognised in the literature regarding termination of pregnancy (TOP) care that it causes deleterious effects on those caring. Though this has been widely accepted there have been no studies, looking at student nurses lived experience in this area of care. With the increasing advancements in technology and nurses autonomy, day case TOPs are set to increase. With student regularly placed on day surgery units there is a need to explore how this will affect student nurses while on placement. Aim - To investigate student nurses’ lived experiences of caring for women undergoing a termination of pregnancy. Methodology and methods - A qualitative hermeneutic phenomenology research approach was used. Obtaining the data through phenomenological semi- structured interviews of four student nurses retrospective accounts of TOP care. They were then analysis using interpretive phenomenological analysis. Findings - During student nurses lived experience of TOP care they suffered an emotional burden. Within this emotional burden, various stressors made them elicit closed-off, withdrawn or emotionally attached coping response. These stressors include; the 'Termination of life', 'Apprehension of the unknown', 'Challenging patients' and the 'Care environment'. There were certain mediators of these stressors this included support. There were some predicaments of accessing this support while on placement. Conclusion - TOP care affected the emotional attributes of the student nurses. The stressors they experienced on placement caused them to elicit negative coping responses. These findings provide a different perspective to the existing literature. Abstract 2 Recommendations - Following the Lazarus Transactional Model of Stress and Coping recommendations on extra mentorship and information throughout the students placement were made at different organisational levels.